Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 1866 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Eulaema meriana (Olivier, 1789)" ] } The dataset includes 1866 records from 16 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007052-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences